Upaya Pengendalian Kebakaran Hutan di Taman Wisata Alam Gunung Guntur, Garut - Lailan Syaufina; Muhammad Hawari Azka (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2021)
Forest fires are one of the forest disturbances that can damage ecosystems. Forest fires in Guntur Mountain Nature Tourism Park in the last five years have a high frequency, so that efforts to control forest fires are needed. The purpose of this reasearch to identify, describe, analyze control efforts and the role of the community in forest fires. The method used in this research is data triangulation and analyzed descriptively qualitatively. The selection of research subjects using method of snowball sampling technique. Forest fire control efforts are carried out by the government and community. The results of this research show that forest fire prevention efforts are carried out by installing warning boards, having partners with community associations and conducting socialization to communities around the forest. The number of community participation in the socialization was 53,33%. The number of community participation reporting of forest fires was 60%. The number of community participation in suppression is 63,33%. Keywords: Guntur Mountain, extinguishing, natural tourism, reporting, socialization